Economic Co-operation of the Regions of Russia with Turkmenistan - Vyacheslav Vashanov; Jahan Orazdurdiyeva (European Regional Science Association (ERSA), 2005)
Among the CIS countries Turkmenistan is known as one of the most closed state, information about which could hardly be found. At the same time these dates are contrary to each other. Meanwhile, Turkmenistan, a former Soviet Central Asian republic of almost 5 million people, has a lot of potential. It is rich in oil and gas. Proven gas reserves amount to at least 100 trillion cubic feet, and possibly 260 trillion, putting Turkmenistan among the world's top 10 countries in terms of such reserves. Untapped oilfields lie off the coast in the Caspian Sea, the size of which is yet to be quantified. Being among the richest countries in the world in terms of hydrocarbon resources, Turkmenistan represents unquestionable interest for European community as an oil and gas exporter and interests at the world's energy markets as well. The page gives some aspects of foreign economic activity based on analysis of the regional co-operation between Russian Federation and Turkmenistan. The paper puts to the center of research the following issues: a) classification of the Russia's regions according to the level of commodity circulation; b) peculiarity of the trade links between Russia and Turkmenistan at the oil and gas, food, chemical and mechanical engineering fields; c)to determine export/import oriented regions. The purpose of the page is to investigate the present level of Russia-Turkmenistan co-operation, find out the ways to be integrated to the European's energy markets.
Keywords: 330